The Diagnosis of Minimal Change Disease in Diabetic Nephropathy - M. Barry Stokes (The Scientific World Journal)
Proteinuria is common in diabetic patients and usually reflects the presence of diabetic glomerulosclerosis. This paper reviews the differential diagnosis of proteinuria in diabetic patients and discusses the role of renal biopsy examination in identification and management of minimal change disease in this cohort. Identification of nondiabetic glomerular disease requires careful correlation of clinical history and renal biopsy findings and may have important implications for prognosis and therapy.